2006
DOI: 10.1080/00016480500280140
|View full text |Cite
|
Sign up to set email alerts
|

Benign paroxysmal positioning vertigo: A long-term follow-up (6–17 years) of 125 patients

Abstract: The recurrence rate in patients with a mean follow-up of 10 years was 50%. Most recurrences (80%) were within the first year after treatment, irrespective of the liberatory maneuver applied. None of the patients observed a recurrence after a symptom-free period of 8 years. Recurrences were seen significantly more often in women (58% versus 39%). The recurrence rate of patients in the seventh decade was half that of those in the sixth decade (p=0.0009). A history of three or more BPPV attacks prior to treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
5
32

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 9 publications
6
88
5
32
Order By: Relevance
“…Recurrence varied between 10.0% and 80.0% of the cases treated according to Brandt et al 29 and Simhadri et al 30 . Semont 31 reported it in 4.2% of his patients and Baloh 20 reported a recurrence rate of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence varied between 10.0% and 80.0% of the cases treated according to Brandt et al 29 and Simhadri et al 30 . Semont 31 reported it in 4.2% of his patients and Baloh 20 reported a recurrence rate of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…However, one cross-sectional study showed a recurrence rate in 56% of affected individuals within one year 2 . Cases of recurrence mostly happened (80%) within the first year after treatment, irrespective of the maneuvers applied 29 . Five of our patients (13.5%) had BPPV recurrence, of which two had PC-BPPV episodes three and six months prior to their medical visits, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…), которые представ-ляют собой повороты головы и туловища па-циента, производимые в определенной последо-вательности и темпе, что приводит к возврату отолитов из полукружного канала в мешочек. В литературе приводятся данные о полном из-лечении 83 % пациентов с ДППГ после одно-кратного вестибулярного маневра, выполненного специалистом (отоневролог, вестибулолог) [16]. Использование специальных позиционных ма-невров Семонта и Эпли в 90 % случаев позво-ляет улучшить состояние пациентов с ДППГ в течение недели [17].…”
Section: патогенетическая терапия вестибулярных расстройствunclassified
“…Вестибу-лярная реабилитация преследует 3 основные цели: тренировка стабилизации взора, трени-ровка устойчивости, уменьшение субъективного головокружения. При проведении вестибуляр-ной гимнастики (реабилитации) необходимо со-блюдать ряд принципов: регулярность занятий (ежедневно), постепенное возрастание вестибу-лярных нагрузок, упражнения выполняются до появления головокружения, составление пись-менных инструкций для выполнения упражне-ний [16,20,21].…”
Section: реабилитация в виде вестибулярной гимнастикиunclassified